Mediating Matonge: Relocations of Belgian Postcoloniality in Four Films - Arnaut, Karel (Afrika Focus, 2019)
In this paper I look at the Matonge neighbourhood of Brussels as a locus of postcolonial and diasporic imagination and activism by different groups and individuals most notably people who identify as Africans, Belgians with African roots, or ‘Black’ in Belgium. Within a longer historical narrative that starts in the late 19th century, I focus on the period beginning in the late 1980s when new migrational flows from Africa and other southern countries into Brussels make the Matonge quarter increasingly visible in an otherwise hesitantly globalizing Belgian/European metropolis. This issue is taken up by several filmmakers who, over the last thirty years, have situated their critiques of the Belgian postcolonial condition in ‘Matonge’. In this paper I briefly present four of these films in order to illustrate the ways in which ‘Matonge’ features in changing discourses concerning inequality, cultural affirmation, and diasporic activism. KEYWORDS: MATONGE, BRUSSELS, POSTCOLONIAL CONDITION, MEDIA AND MEDIATION